Pengaruh Perbedaan Metode Inkubasi Telur Terhadap Tingkat Penetasan Telur Lobster Air Tawar (Cherax quadricarinatus) - Tamima, Nani I (e-Journal BUDIDAYA PERAIRAN, 2014)
The important thing in cultivation of freshwater crayfish is the availability and quality of seed. The use of appropriate method could support the production of good seed, therefore in this research we conduct the seed production methods, one is hatching in a natural way, while the other is separating the eggs from the female. On this research, we used 5 females and 3 males of freshwater crayfish (LAT) and placed them in a round glass fiber container with a diameter of 1.5 together with aeration and small pipe (as shelter).  Initial average weight of the female and male, respectively from 74.5 to 76.7 grams and an average length of 6 cm. These female and male freshwater crayfish were acclimatized before spawning. Gonadal maturation performed together in a single glass fiber container for 2 months.  In this study routinely measured water quality parameters including temperature, acidity (pH) using cremometer, also dissolved oxygen and CO2. Egg test used for this study was given as treatment A which is 150 eggs incubated by each female and treatment B which is 150 eggs separate from each parent and left to hatch by itself.  Females that incubate their eggs and the separating eggs were placed in different aquarium (60 x 40 x 40 cm) equipped with modified pipes for shelter. The results of water quality parameter are temperature 24.5-26.5 oC, pH 7, DO 6.43 ppm and CO2 0.04 ppm. Egg incubation period lasts for 45 days.  From this research the following conclusions can be drawn between the two treatments were performed in the study, natural incubation method gives much better results for egg hatching of freshwater crayfish.   Keywords: egg incubation method, freshwater crayfish, Cherax quadricarinatus, reproduction